PENGARUH KEPUASAN KERJA DAN MOTIVASI KERJA TERHADAP KOMITMEN ORGANISASIONAL DAN KINERJA KARYAWAN DI KANTOR PALANG MERAH TIMOR LESTE - Glorita Luisa Dos Santos Belo, Elisabeth; Riana, Gede; Priartrini, Putu Saroyeni (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME 03.NO.12.TAHUN 2014, 2015)
This study examined about the influence of job satisfaction and work motivation against the organizational commitment and employee performance. The samples using a proporrionate stratified random sampling technique and based on predetermined criteria, the sample size was 99 respondents. The results showed that influence existence is directly significant positive on job satisfication, work motivation, organizational commitment against the employee performance
Keywords: Satisfaction, Motivation, Commitment, Performance